Model Promosi Kesehatan Bidan Pada Ibu Hamil Pre Eklamsi Berdasarkan Stage Of Change (Kajian Transtheory Model) - Jamhariyah, Jamhariyah; Sugijati, Sugijati; Prijatni, Ida (Malang Journal of Midwifery (MAJORY), 2020)
Complications that need to occur in pregnant women and need to be done is preeclampsia. From 2012 to 2016, pre-eclampsia was ranked as the first cause of AKI in East Java, the case of preeclampsia in 2016 was 30.90% (1). In Jember in 2015 there were 31 cases of preeclampsia deaths. Data from the Ajung Puskesmas (2017) were 45 preeclampsia cases from January to September. A preliminary study of 10 preeclampsia TM III pregnant women, using a structured interview method, obtained 6 mothers undergoing routine checks with a record of 3 mothers achieving success but not yet performing optimally. The purpose of this research is to make a model of health promotion for midwives in pregnant women with Trimester III preeclampsia based on the Change Phase. The design of this study is quasi-experimental. Sampling using simple random sampling technique totaling 75 respondents. R&D research. Instrument questionnaire sheet. Obtained differences after being given bidkes based on the stage of change. Statistical test analysis with the value of Pre Conteplation Z count (-7,022)> Z Table 0.05 (1.96) so that Ho is rejected, the value of Pre Conteplation is increasing, Hi Conteplation Z count (-6,244)> Z Table 0.05 (1 , 96) so that it can quickly increase the value of increased conteplation. Preparation Stage Calculated Z values ??(-7,253)> Z Table 0.05 (1.96) Ho is rejected the value of increasing contemplation. Action stage Z count (-6,304)> Z Table 0.05 (1.96) so that Ho is rejected the value of Conteplation increases. Changing the behavior of preeclampsia requires a health promotion model that is informed according to policy level. Keywords: Preeclampsia Pregnant Women, Promotion Model, Stage of Change